Challenges in characterization of GNSS precise positioning systems for automotive - Pendão, Cristiano Gonçalves (2020)
Autonomous driving is currently one of the main focuses of attention in the automotive industry. A requirement for efficient and safe driving of autonomous vehicles is the ability to precisely pinpoint the location of the vehicle, in the decimeter- to centimeter-level on a global scale. GNSS is expected to play a major role in providing accurate absolute and global positioning, yet many challenges arise in dense urban environments due to lack of line-of-sight to satellites and multi-path, decreasing availability and accuracy. Also, the position accuracy announced by GNSS receiver manufacturers is rather optimistic, typically obtained in best-case scenarios. However, this is rarely encountered in real-world driving conditions, especially in urban areas, leading to a mismatch between receiver specification and real world performance. This paper provides a systematic study regarding the requirements, methods, and solutions available for the characterization/evaluation of a GNSS po- sitioning system in real world driving conditions. An architecture for a precise Automotive Global Reference System (centimeter-level), able to characterize a decimeter-level accuracy GNSS position- ing system in dynamic conditions, is proposed. To the best of authors’ knowledge, such a study is not available in the literature.